An Assessment of Information and Communication Technology (ICT) Resources at a Higher Education Institution in Namibia (International Journal of Scientific Research and Management (IJSRM), 2025)
The main purpose of this paper is to examine the Information Communication Technologies (ICT) resources employed at a certain university campus in Namibia. The paper mainly concentrate on the implementation elements such as availability, adequacy as well as accessibility of the ICT resources at the university campus. The paper reviewed the literature specifically concerning the effect of ICT resources towards students learning activities. Through a quantitative approach, an online questionnaire was designed to understand the questions related to the objectives of the study. A sample of 130 students through convenience sampling technique was selected from the population of students enrolling in various degree programs at the university campus. This quantitative study’s primary aim was to assess variables using descriptive and inferential statistics concerning the phenomenon. The study results shows that students at that specific campus are of the perspective that educational technologies are supportive for their academic achievements. Furthermore, the paper revealed that students are of the perspective that the ICT resources availability, adequacy and accessibility currently at that university campus seems not ideal. The study offers practitioners, education officers and researchers a blueprint for designing an educational environment that supports effective students learning, specifically at the Higher learning institution level.